Concept and Practice of Tarbiyatun Nafs in Formal and Informal Educational Institutions: (A Comparative Study of UIN North Sumatra and Jabal Hindi Thariqah) - Safria Andy; Uqbatul Khoir Rambe (At-Ta'dib, 2023)
This research aims to understand how soul education (tarbiyatun nafs) is implemented at the State Islamic University of North Sumatra and the Jabal Hindi Thariqah in shaping students and pupils with noble character, intelligence, caring, and well-mannered. By combining knowledge and virtuous conduct, intelligence is the main objective of this research in the two locations. The methodology used is qualitative field research, employing descriptive analysis with the results based on descriptive phenomena and participatory observation. The research was conducted at the State Islamic University of North Sumatra and the Naqshbandiyah Jabal Hindi Thariqah to examine the concepts of soul education held by both institutions and to compare these concepts as a means towards achieving true soul education in the field of Education, ultimately contributing to the development of a morally upright society. The findings reveal that the State Islamic University of North Sumatra has developed an educational concept that integrates moral excellence into every aspect of campus life, with the entire campus community directed towards goodness, serving as role models and fostering ideal imagination. It acts as a stimulus and catalyst for the students' personalities through spiritual and physical guidance. The Naqshbandiyah Jabal Hindi Thariqah places the soul as a faith that can be attained through contemplation, reflection, and remembrance, leading to the purification of the heart and soul (tazkiyatul qalb and nafs) achieved through spiritual practices to attain the pleasure of Allah. It stems from the servant's love towards Allah SWT and strengthens the physical body to achieve success (economically) to establish prosperity and noble civilization. The results of this research can be compiled into a textbook and contribute to society, especially for students and pupils.